Archimedean solids: Transition metal mediated rational self-assembly of supramolecular-truncated tetrahedra - Leininger, Stefan (The National Academy of Sciences, 2000)
A family of nanoscale-sized supramolecular cage compounds with a polyhedral framework is prepared by self-assembly from tritopic building blocks and rectangular corner units via noncovalent coordination interactions. These highly symmetrical cage compounds are described as face-directed, self-assembled truncated tetrahedra with T(d) symmetry.